District Assemblies, Ngos And Local Development In Ghana: The Case Of Agona West Municipality - Arthur, L. (University of Ghana, 2015)
This research investigated the performance of Agona West Municipal Assembly (AWMA) as a District Assembly (D.A.) in the delivery on its developmental mandate in the areas of infrastructure, education and health as well as the contributions of Non Government Organizations (NGOs) in the same areas of developments. The study found out that, concerning infrastructural development, AWMA has been constructing markets, toilet facilities, roads, extending pipe borne water and bore holes and installating street lights in the AWM despite the development constraints the assembly faces. On their part, NGOs were not really active in infrastructural developments due to resources constraints and their selective operations as non state actors in local development at the AWM. In education, due to resources and other development constraints, AWMA has been prioritizing the constructions of classrooms, Ghana School Feeding Programme (GSFP) kitchens, bungalows, Early Childhood Centre as well as supply of furniture among others. The contributions of NGOs in education have also been, sponsorship of students, building and renovation of unit classrooms, donating of educational materials to schools and placing foreign volunteers to schools to teach among others. In health, AWMA has been engaged in the constructions of nurses‟ quarters, clinics and CHPS compounds and supply health care equipments and materials. On their part, the NGOs have been engaging in health outreach programmes, supply of medical equipments and placement of volunteers to health centers among others. The study also found out that, AWMA faced the challenges with revenue mobilization as the major source of development constraints, excessive partisanship, challenges with coordination between AWMA and NGOs among others.
Thesis (MPhil)
Keywords: District Assembly; NGOs; markets; toilet facilities; pipe borne water